The pin drop principle : captivate, influence, and communicate better using the time-tested methods of professional performers - Lewis, David H., 1970- (Jossey-Bass, 2012)
"Tap into the powerful techniques of professional actors and great communicators The Pin Drop Principle is a step-by-step master class for anyone wishing to become a more confident and credible communicator. Lewis and Mills believe all business professionals ought to deliver their message in such an engaging way that one could literally hear a pin drop when they speak. The secret to doing so comes from an unusual world: professional acting. By activating "objective" and "intention"--The main tools of actors (and great communicators)--business people can give their messages meaning and relevance, so the recipients walk away knowing why the message is important and what is in it for them. Empowers business professionals with performance-based delivery techniques--from storytelling to vocal dynamics--essential to becoming a great communicator Written for anyone wishing to engage listeners, establish instant credibility, influence key decision makers, and create a positive lasting impression Based on the Pinnacle Method, one of the most popular and groundbreaking communication skills training methods The Pin Drop Principle is an accessible resource for anyone who routinely needs to present ideas to large or small groups, convey feedback effectively, conduct difficult conversations, and persuade others"--